THE EFFECT OF PROMOTION STRATEGIES AND PRICE ON CONSUMER SATISFACTION FOR BOUQUET PRODUCTS IN CURAH TATAL VILLAGE, ARJASA SUBDISTRICT, SITUBONDO REGENCY - Mujiyanti, Sri Ayudha; Maulida, Shinta Nur; Sri D, Lusi Endang (Yayasan Amanah Nur Aman, 2025)
In an era of globalization and increasingly fierce market competition, companies are required to be smarter in designing effective marketing strategies. One important element in marketing strategy is promotion, which serves to increase consumer awareness and interest in products. In addition, price is also a crucial factor that can influence purchasing decisions and consumer satisfaction. In this context, bouquet products, which are aesthetically arranged compositions of flowers, have become increasingly popular among the public, especially for various events such as weddings, birthdays, and other celebrations.